The Economic Returns of Network Resources to the Urban Informal Economy: Evidence from Street Vendors in Addis Ababa, Ethiopia - Kebede, Getahun Fenta; Odella, Francesca (European Journal of Sustainable Development, 2014)
It is widely recognized that social capital constitutes an important form of social regulation in informal sector and it is the major component of the asset portfolios of the urban poor. Nevertheless, the potential contribution of social capital in the informal sector remains under-investigated in African cities. Applying the network approach, this study examined the economic returns of social capital to microenterprises in the informal sector. To do so, the personal networks of street vendors in Addis Ababa were examined. Multi-stage sampling procedures involving purposive and systematic random-walk techniques were applied to draw samples. Data were collected through position generator surveys. The data were analyzed using OLS and Instrumental Variable Estimators. By controlling the potential endogeneity, the estimation results revealed that network resources are positive and significant predictors of enterprise profit. But their benefit is less for married vendors than unmarried ones. The human capital measures such as education, vocational training, and business experience are not significant predictors of enterprise profit. Key Words: Social Capital, Social Networks, Informal Sector, Ethiopia, Addis Ababa